Prosthetic Valve Endocarditis with aortic root abscess - Padmaja, Kanne; Lakshmi, Vemu; Amaresh, Mallempati; Mishra, Ramesh; chikkala, Rosy; Sritharan, Venkataraman (International Journal of Infection Control, 2013)
Abstract: A young patient with congenital aortic stenosis and aortic valve replacement developed Prosthetic valve endocarditis (PVE) and aortic root abcess due to Achromobacter.xylosoxidans subsp denitrificans. PVE with this organism is rare and only 3 cases have been reported in the literature. Patient had an uneventful recovery with appropriate antibiotic therapy.